Renal changes and acute kidney injury in covid-19: a systematic review - Nogueira,Samuel Átila Rodrigues (2020)
SUMMARY OBJECTIVE We aimed to present a review of renal changes in patients with COVID-19. METHODS We performed a systematic review of the literature to identify original articles regarding clinical, laboratory, and anatomopathological kidney changes in patients infected with SARS-CoV-2 published until May 7, 2020. The search was carried out across PubMed, Scopus, and Embase using the keywords “COVID-19”, “coronavirus”, “SARS-CoV-2”, “kidney injury” and “kidney disease”. Fifteen studies presented clinical and laboratory renal changes in patients with COVID-19, and three addressed anatomopathological changes. DISCUSSION Acute kidney injury (AKI) was a relevant finding in patients with COVID-19. There were also significant changes in laboratory tests that indicated kidney injury, such as increased serum creatinine and blood urea nitrogen (BUN), proteinuria, and hematuria. The presence of laboratory abnormalities and AKI were significant in severely ill patients. There was a considerable prevalence of AKI among groups of patients who died of COVID-19. Histopathological analysis of the kidney tissue of patients infected with SARS-CoV-2 suggested that the virus may directly affect the kidneys. CONCLUSION Although COVID-19 affects mainly the lungs, it can also impact the kidneys. Increased serum creatinine and BUN, hematuria, proteinuria, and AKI were frequent findings in patients with severe COVID-19 and were related to an increased mortality rate. Further studies focusing on renal changes and their implications for the clinical condition of patients infected with the novel coronavirus are needed.